Intraoperative evaluation of polymorphonuclear leukocyte during second-stage revision surgery promote overdiagnosis of persistent periprosthetic joint infection - Saitoh, Yoshinobu (Acta Orthop Traumatol Turc, 2018)
OBJECTIVE: The aim of this study was to evaluate whether intraoperative histopathological examination could predict the risk of relapse of infection in periprosthetic joint infections (PJI). METHODS: The study included 25 patients (14 women and 11 men, with a mean age of 67.0 years (range, 37–83 years)), who had two-staged revision surgery for a PJI. Following prosthetic removal in the first stage, all patient underwent an intraoperative histopathological examination during the second stage. The patients were divided into PMNs-positive group (≥five PMNs per high-powered field) or -negative group (<five PMNs). A relapse was defined as the occurrence of PJI. Median follow-up was 51 months (range, 32–80 months) following second-stage revision surgery. RESULTS: Intraoperative histopathological revealed that 8.0% of cases were PMNs-positive. Postoperative histopathological examination revealed that 28.0% of cases were PMNs-positive. 28.0% of cases showed discrepancy between the PMNs-positivity. Intraclass correlation coefficient indicates poor reproducibility. Infection relapse after revision surgery occurred in two cases (8.0%); both relapse cases were from the PMNs-negative group. There was no statistical relationship between the presence of PMNs in periprosthetic tissue by intraoperative or postoperative histopathological examination and relapse of infection. CONCLUSIONS: Our findings showed that intraoperative histopathological examination could not predict the relapse of infection. Intraoperative histopathological examination promotes overdiagnosis of the requirement for re-implantation of antibiotic-impregnated cement and prolonged treatment periods. LEVEL OF EVIDENCE: Level III, diagnostic study